Secure unicast position-based routing protocols for Ad-Hoc networks - Qabajeh, L.K.; Kiah, M.L.M.; Qabajeh, M.M. (2011)
Ad-Hoc networks are decentralized wireless networks. A fundamental problem in Ad-Hoc networks is finding a secure and correct route between a source and a destination efficiently. The need for scalable and energy efficient routing protocols, along with the availability of small, inexpensive and low power positioning instruments, results in making position-based routing protocols a promising choice for mobile Ad-Hoc networks. This paper presents an extensive overview of the existing Ad-Hoc unicast routing protocols that make forwarding decisions based on the geographical position of the destination of a packet, while keeping security issues in mind. We outline the main problems for this class of routing protocols and a qualitative comparison of the existing protocols is done in regards to both security and performance issues. We conclude our work by investigating some future research opportunities.